2006
DOI: 10.1158/1078-0432.ccr-06-0606
|View full text |Cite
|
Sign up to set email alerts
|

Approval Summary: Nelarabine for the Treatment of T-Cell Lymphoblastic Leukemia/Lymphoma

Abstract: Purpose: To describe the clinical studies, chemistry manufacturing and controls, and clinical pharmacology and toxicology that led to Food and Drug Administration approval of nelarabine (Arranon) for the treatment of T-cell acute lymphoblastic leukemia/lymphoblastic lymphoma. Experimental Design: Two phase 2 trials, one conducted in pediatric patients and the other in adult patients, were reviewed. The i.v. dose and schedule of nelarabine in the pediatric and adult studies was 650 mg/m 2 /d daily for 5 days an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 9 publications
0
55
0
1
Order By: Relevance
“…Thus, we evaluated the potential of ara-G for ATL cells in vitro. The intracellular accumulation of ara-GTP was greatest in cells of T-lymphoid lineage compared with other cell types, thereby conferring ara-G cytoreductive effects specifically on T-cell malignancies (1)(2)(3)(6)(7)(8). Clinical response to nelarabine in hematologic malignancies was associated with higher intracellular ara-GTP concentrations (4,5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we evaluated the potential of ara-G for ATL cells in vitro. The intracellular accumulation of ara-GTP was greatest in cells of T-lymphoid lineage compared with other cell types, thereby conferring ara-G cytoreductive effects specifically on T-cell malignancies (1)(2)(3)(6)(7)(8). Clinical response to nelarabine in hematologic malignancies was associated with higher intracellular ara-GTP concentrations (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic evaluation of ara-GTP will provide crucial information to optimize ara-G therapy (3)(4)(5). Clinical data have already confirmed that response to nelarabine is associated with higher intracellular ara-GTP concentrations in both acute and indolent leukemias (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relapsed ALL in an adult is not curable, but remissions are sometimes achieved with re-induction with either a standard vincristine, prednisone and anthracycline or with a cytarabine-based regimen, particularly high-dose Ara-C combined with an anthracycline or clofarabine. [31][32][33] Available data from the IBMTR show that patients transplanted from an HLA-identical sibling for ALL in second CR (CR2) have approximately a 35-40% chance of long-term DFS, while those transplanted with disease not in remission have a DFS of only 10-20%. 34 Figure 4 shows the overall DFS for patients with ALL, depending on their remission status, who underwent allogeneic transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Следует отметить, что результаты лечения не зависели от варианта ТГСК и были одинаковыми при алло-и аутоТГСК [24]. В другом исследовании было показано, что несмотря на одинаковые показатели ОВ при проведении аллоТГСК и аутоТГСК (36 и 39 % соответственно) частота повторных рецидивов ЛБЛ при проведении аллоТГСК существенно ниже [25][26][27]. Данный факт, вероятно, объясняется эффектом «трансплантат про-тив опухоли», который реализуется в случаях алло-ТГСК.…”
unclassified